Employers’ Feedback on Davao Oriental State College of Science and Technology (DOSCST) Professional School Graduates in their Workplace - Saturnino Dalagan, Jr. (Davao Research Journal)
This study was conducted to determine how the Davao Oriental State College of Science and Technology (DOSCST) Professional School graduates performed in the real work environment as perceived by their employers. It utilized the quantitative method with 52 employers as the respondents and the qualitative method with 11 employers as the key informants. The study was conducted at the different workplaces of the DOSCST Professional School graduates within the province of Davao Oriental. Findings reveal that the level of employers' satisfaction with the education exemplified by DOSCST Professional School graduates is highly satisfactory. The degree of importance for the successful performance of the graduates in terms of the four indicators: knowledge and understanding of the job, general skills, specialized skills, and qualities of graduates, is extremely important. However, the employers' satisfaction and the DOSCST Professional School graduates' performance indicate an overall significant positive moderate relationship towards each other. Among the demographics given in this study, only the length of service exhibits a significant difference in the employer's satisfaction. Moreover, future researchers may study students' academic performance versus the teaching performance of the DOSCST Professional School graduates. Likewise, they may also look into the ethics and commitment of the teachers who graduated from the DOSCST Professional School.